(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Pain is a common complaint following stroke, reported in 11- 55% of stroke survivors. Central Post Stroke Pain (CPSP) is a central neuropathic pain condition in which pain arises as a direct result of a cerebrovascular lesion in the central somatosensory nervous system. In this study efficacy of duloxetine in treatment of CPSP was evaluated and compared with pregabalin. Materials and methods: This was a single center open-label clinical trial conducted in the Department of Neurology, Dhaka Medical College Hospital, from July 2012 to November 2012. Initially 193 participant were invited. Patients of CPSP were randomized to receive 60 mg/day duloxetine or 300 mg/day pregabalin. Pain score were recorded using Visual Analogue Scale (VAS) on day 0, 6 week and 12 th week. Data was collected through prede- signed questionnaire. Data was entered and analyzed using SPSS version 22..0. Results: In duloxetine group, mean VAS score decreased from 6.8 ± 0.91 to 3.01± 1.12 with 12 weeks of therapy. In pregabalin group, the mean VAS score decreased from 6.99 ± 1.22 to 4.91 ± 0.82 with 12 weeks therapy . At 12 weeks, duloxetine showed statistically significant low VAS scores than pregabalin. Adverse events were reported in 17.9% of the participants. Lathergy/ somnolence (8.1%) and peripheral edema (3.4%) were commonly reported in the pregabalin group and constipation (6.9%) and orthostatic hypotension (4.6%) were commonly reported in duloxetine group. Conclusion: In this study, duloxetine 60 mg is statistically more efficacious than pregabalin 300 mg in reducing central post stroke pain. Both duloxetine and pregabalin have a promising safety profile and well tolerated. JCMCTA 2020 ; 31 (2) : 10-13